2017
DOI: 10.1111/ppc.12220
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of health anxiety and related factors in Chinese patients with physical disease

Abstract: Nurses should pay more attention to the HA of patients with physical diseases. Appropriate psychological interventions need to be used to improve patients' HA and QoL.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(7 citation statements)
references
References 32 publications
(62 reference statements)
0
7
0
Order By: Relevance
“…Previous research suggests that HA is common in individuals with physical diseases. 2,28 We found that extraversion was negatively correlated with HA, which suggests that extraversion should protect individuals against HA. These findings support those of previous studies.…”
Section: Discussionmentioning
confidence: 70%
See 3 more Smart Citations
“…Previous research suggests that HA is common in individuals with physical diseases. 2,28 We found that extraversion was negatively correlated with HA, which suggests that extraversion should protect individuals against HA. These findings support those of previous studies.…”
Section: Discussionmentioning
confidence: 70%
“…For example, our previous study found that HA prevalence levels varied by clinic: cardiology (47.69%) had the highest prevalence, followed by rheumatology (47.17%), neurology (42.62%), rehabilitation (41.94%) and endocrinology (34.48%). 2 One study found that 8% to 11% of genitourinary patients had HA. 15 We found that HA was more prevalent in medical employees than reported in these previous studies, and higher than in some patients.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Health anxiety (SA) is defined as a multidimensional concept with cognitive, emotional and behavioral dimensions (20). Epidemiological research, on the other hand, defines the health anxiety as the fear of both ordinary and unusual bodily sensations, negative interpretation of fears and mental symptoms associated with fears (22). The individual believes that his/her health problems are not taken seriously enough and develops wrong strategies to deal with his/her health problems.…”
Section: Discussionmentioning
confidence: 99%